USE OF SOCIAL MEDIA FOR SEEKING HEALTH-RELATED INFORMATION AMONG CARDIAC PATIENTS.: J Peop Univ Med Health Sci. 2025:15(3), 139-143. http://doi.org/10.46536/jpumhs/2025/15.03.669 - Syed Fayaz Mujtaba¹, Mashooq Ali Dasti², Sajid Ali³, Altaf Hussain⁴, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: The use of social media for seeking health-related information among cardiac patients has gained significant attention, particularly as digital platforms have transformed how individuals access and share health information. This article explores the multifaceted role of social media in facilitating health information seeking behavior, especially in the context of cardiovascular health. OBJECTIVE: Therefore, the aim of this study was to determine prevalence of use of social meid in patients with ischemic heart doses who underwent intervention. METHODS: This study was conducted at Larkana Satellite Center of National Institute of Cardiovascular Diseases (NICVD), Pakistan from November 2024 to April 2025. Patients who underwent cardiac Intervention within one month were enrolled in this study. Patients were interviewed regarding their Basic demographics, profession, level of education. Patients were interviewed to determine frequency of use of social media, type of social media, and duration of social media. They were also asked what type of content they seek on social media. RESULTS: A total of 253 patients were included in this study out of which 162(68.9%) were males and 73(31.15%) were females. 182 (77.4 %) were Sindhi speaking while remaining were siraiki, balochi, Brohi Urdu and others. 121 (51.5%) were not educated. Almost 80 (34%) used one or other form of social media. 75 (31.9%) used Facebook. 37 (15.7%) used YouTube. Among them only 7 (3%) use social media for health related material. CONCLUSION: social media use is common in patient with cardiac disease. But very few use this medium for seeking health related information.